Industry Needs Analysis for Augmented, Virtual and Extended Reality: Addressing Skills Gaps in Immersive Technologies for Economic Development - Sánchez-García, Javier; Callarisa-Fiol, Luis Jose; Fandos-Roig, Juna Carlos; Tena-Monferrer, Sandra (JOINETECH, 2025)
The rapid advancement of augmented reality (AR), virtual reality (VR), and extended reality (XR) technologies presents unprecedented opportunities for economic innovation and sectoral transformation. However, significant skills gaps persist across European industries, limiting the sector’s capacity for innovation and competitiveness. This study presents a comprehensive industry needs analysis conducted across ten countries (Turkey, Romania, Spain, South Africa, Bulgaria, Germany, Greece, Sweden, Slovakia, and Israel) through 200 in-depth interviews with 160 companies. The research, conducted between September and October 2024 as part of the Metaverse Academy Project, identifies critical skills requirements, training needs, and barriers to adoption of immersive technologies. Key findings reveal high awareness of these technologies but variable adoption rates, a significant multidisciplinary skills gap encompassing technical, creative, and soft skills, and a strong need for industry-academia collaboration. The analysis provides evidence-based recommendations for developing comprehensive training programmes aligned with industry needs, thus contributing to the European Union’s competitiveness in the immersive technologies sector.